Research and Application of Visualization Technology of Water Diversion in Hanjiang-Rongjiang-Lianjiang River Water System Connectivity Project - LI Jiasheng; CHEN Longzan; LI Jin; JIANG Yutian; XUE Xiaopeng (Renmin Zhujiang)
On the basis of the Hanjiang-Rongjiang-Lianjiang river connectivity project,through the research on the flow data processing and the flow evolution display technology,this paper creatively proposes the flow data processing with data cleaning,standard storage and structured organization as the main contents,and determines the display technology of various elements according to the different classification of the flow elements,and finally visually displays the water level and flow velocity in combination with water diversion examples.The research shows that the visualization technology of the dynamic evolution of Hanjiang-Rongjiang-Lianjiang river is fast in rendering and rich in visual content,which provides good support for the connectivity effect and decision evaluation of the Hanjiang-Rongjiang-Lianjiang river system.